Three strange things in solar still - Khechekhouche, Abderrahmane (Kasdi Merbah University, Ouargla, 2024)
Solar stills are widely recognized for their simplicity and potential in providing potable water in remote and resource-scarce regions. However, their low productivity remains a persistent challenge. This paper presents an exploration of three unconventional experiments aimed at enhancing or evaluating the performance of solar stills, each yielding surprising outcomes. 1. Plastic Fins for Enhanced Evaporation The first study investigated the role of surface tension in evaporation rates by introducing plastic fins into the basin of conventional solar stills. The fins, extending above the water layer, aimed to spread water over their surfaces, thereby increasing evaporation rates. Three designs were tested, each with different fin diameters: 0.5 cm, 1 cm, and 1.5 cm, and were compared to a reference solar still (RSS). The results were remarkable: the 0.5 cm fin diameter model (MSS1) achieved the highest productivity of 6176 ml/m² per day—a 41.4% improvement over the RSS, which produced 4368 ml/m² per day. These findings highlight the significant potential of optimizing solar stills through innovative design modifications. 2. Natural Sand Integration: An Unexpected Outcome In the second study, natural sand dunes from the El Oued South region of Algeria were tested as a productivity enhancer for a single-slope solar still with a basin water thickness of 1 cm. The sand layer covered the entire basin surface, hypothesized to improve thermal absorption and enhance evaporation. Contrary to expectations, the results showed a 1.46-fold decrease in distilled water productivity compared to the baseline. This counterintuitive outcome suggests that sand's thermal properties or its interaction with water dynamics in the basin might hinder rather than help productivity, necessitating further investigation. 3. Double Glazing: A Misstep in Innovation The third experiment explored the use of double-glazing technology, commonly employed to improve thermal efficiency in solar collectors, applied to a solar still. A 1 cm gap between two glass covers was introduced in a distiller of 0.5 × 0.5 m dimensions. Surprisingly, this modification resulted in a 56.52% reduction in yield compared to the conventional solar still. This finding underscores the complexity of heat transfer and evaporation dynamics in solar stills and highlights the importance of targeted design modifications over straightforward technology transfers. Conclusion Three experiments demonstrate that even well-intentioned modifications to solar still designs can yield unexpected and sometimes counterproductive outcomes. The remarkable success of plastic fins in enhancing productivity underscores the potential of innovative approaches, while the disappointing results from sand integration and double glazing highlight the challenges of optimizing solar still performance. These findings not only advance our understanding of solar stills but also serve as a reminder of the intricacies involved in sustainable water purification technologies. الملخص تُعتبر المقطرات الشمسية أداة بسيطة وفعّالة لتوفير المياه الصالحة للشرب في المناطق النائية والمحرومة. ومع ذلك، يظل ضعف إنتاجيتها تحدياً مستمراً. يعرض هذا البحث ثلاث تجارب غير تقليدية تهدف إلى تحسين أو تقييم أداء المقطرات الشمسية، وقد أظهرت كل تجربة نتائج مفاجئة. 1. زعانف بلاستيكية لتحسين التبخر في الدراسة الأولى، تم دراسة دور التوتر السطحي في معدلات التبخر من خلال إدخال زعانف بلاستيكية في حوض المقطر الشمسي التقليدي. امتدت هذه الزعانف فوق طبقة الماء بهدف نشر الماء على أسطح الزعانف، مما يزيد من معدلات التبخر. تم اختبار ثلاثة تصاميم بقطر مختلف للزعانف: 0.5 سم، 1 سم، و1.5 سم، وتمت مقارنتها بمقطر مرجعي (RSS). أظهرت النتائج أن نموذج الزعانف بقطر 0.5 سم (MSS1) حقق إنتاجية أعلى بلغت 6176 مل/م² يومياً، بزيادة قدرها 41.4% مقارنة بالمقطر المرجعي الذي حقق إنتاجية قدرها 4368 مل/م² يومياً. تُبرز هذه النتائج الإمكانيات الكبيرة لتحسين أداء المقطرات الشمسية من خلال تعديلات تصميم مبتكرة. 2. استخدام الرمال الطبيعية: نتيجة غير متوقعة في الدراسة الثانية، تم اختبار رمال طبيعية من كثبان منطقة الجنوب الجزائري (الوادي) كعامل لتحسين إنتاجية المقطر الشمسي أحادي الميل، بسمك ماء قدره 1 سم في الحوض. تم تغطية سطح الحوض بالكامل بطبقة من الرمال، على أمل تحسين الامتصاص الحراري وتعزيز التبخر. على عكس التوقعات، أظهرت النتائج انخفاضاً في إنتاجية الماء المقطر بمقدار 1.46 مرة مقارنة بالوضع الأساسي. تُشير هذه النتيجة إلى أن الخصائص الحرارية للرمال أو تفاعلها مع ديناميكيات الماء قد تعيق الإنتاجية بدلاً من تحسينها، مما يتطلب المزيد من الدراسة. 3. الزجاج المزدوج: خطوة غير موفقة استكشفت التجربة الثالثة استخدام تقنية الزجاج المزدوج، المستخدمة عادة لتحسين الكفاءة الحرارية في المجمعات الشمسية، وتطبيقها على المقطر الشمسي. تم وضع غطائين من الزجاج بينهما فجوة 1 سم على مقطر بأبعاد 0.5 × 0.5 متر. بشكل مفاجئ، أدت هذه التعديلات إلى تقليل الإنتاجية بنسبة 56.52% مقارنة بالمقطر الشمسي التقليدي. تُبرز هذه النتيجة تعقيد ديناميكيات انتقال الحرارة والتبخر في المقطرات الشمسية، مما يؤكد أهمية التعديلات المصممة بعناية بدلاً من نقل التقنيات بشكل مباشر. الخلاصة تُظهر هذه التجارب الثلاث أن التعديلات المُبتكرة على تصاميم المقطرات الشمسية يمكن أن تُسفر عن نتائج غير متوقعة وأحياناً غير مُجدية. يوضح النجاح الكبير للزعانف البلاستيكية في تحسين الإنتاجية الإمكانيات الواعدة للتقنيات الجديدة، بينما تُبرز النتائج المخيبة لاستخدام الرمال والزجاج المزدوج التحديات المرتبطة بتحسين أداء المقطرات الشمسية. تُسهم هذه النتائج في تعزيز فهمنا لتقنيات التحلية الشمسية وتُذكّرنا بتعقيداتها، مما يدعم تطوير تقنيات مستدامة لتنقية المياه.
Intervention
Keywords: Solar stills; water purification; plastic fins; evaporation rates; natural sand; double glazing; sustainable technologies; water scarcity; performance optimization; North Africa; المقطرات الشمسية; تنقية المياه; الزعانف البلاستيكية; معدلات التبخر; الرمال الطبيعية; الزجاج المزدوج; التقنيات المستدامة; ندرة المياه; تحسين الأداء; شمال إفريقيا